Diversidad de Cervidae (mammalia, Artiodactyla) en el Pleistoceno de la provincia de Corrientes, Argentina - Alcaraz, María Alejandra (2013)
The study presents an analysis of the peculiar diversity of cervids recorded in two localities at the Corrientes Province (Argentina), Lavalle and Bella Vista. The sediments belong to two successive formations of the late Pleistocene (Lujanian floor/age): Toropí Formation (ca. 52.000 years BP) and Yupoí Formation (ca. 36.000 years BP). The remains are in general antlers, except for a specimen that also preserves partial skull and postcranium. Morenelaphus lujanensis (Ameghino), Antifer ultra (Ameghino), A. ensenadensis (Ameghino), and Hippocamelus sulcatus (Ameghino) are recorded in Toropí Formation, whereas the Yupoí Formation yielded cf. Mazama sp. and Morenelaphus sp. The following issues are discussed: the great diversity of species that include two large forms, A. ultra and A. ensenadensis, and one median to large-size form, M. lujanensis; the record for cf. Mazama in the Pleistocene of Argentina, previously restricted to the Holocene-Present; and the presence of A. ensenadensis in the late Pleistocene outside the Pampean region, expanding its geographic distribution towards northeast Argentina and its biochron beyond the early-middle Pleistocene. Such diversity is remarkable considering other cervid faunas recorded in the late Pleistocene of geographically close areas, like Entre Ríos, Argentina (El Palmar and Tezanos Pinto formations), Uruguay (Sopas Formation), and Southern Brazil (Touro Passo Formation). The greatest specific richness is found in Toropí Formation, which is comparable to that of the late Pleistocene of Sopas Formation, although the age of sediments and the species yielded are not the same.